"Doing" cultural studies: Chua Beng Huat on popular culture. Issue 2 (2nd April 2016) - Morris, Meaghan
ABSTRACT: Focusing on the relationship between Chua Beng Huat's sociological thinking before the Inter-Asia Cultural Studies project and his more recent famous works on consumption and popular culture, this essay seeks to understand how he has produced a methodology and a mode of authority that is effective for the context he inhabits in Singapore as well as resonant for scholars working elsewhere. After discussing his interest in large rather than 'cult' popular cultures, his emphasis on the detail of government processes as well as popular practices, his economically-grounded concept of consumption and his materialist approach to texts, I read his work on 'nostalgia for the kampung' as modelling an Inter-Asian way of doing Cultural Studies that helps us ask questions and develop concepts for our own local contexts.